Temporal variation in Sargassum Biomass, Hypnea epiphytism and associated fauna - Leite,Fosca Pedini Pereira (2003)
Studies were carried out to investigate the temporal variation in Sargassum biomass, Hypnea epiphytism and associated fauna. There was a marked variation in the biomass of Sargassum and Hypnea among various sampling periods. Low values for Sargassum were recorded in August and November, while the lower value for Hypnea biomass was recorded in August. An inverse relationship was found between Sargassum biomass and the intensity of Hypnea epiphytism. The density of the total fauna associated to Sargassum showed a marked reduction in May. This variation was influenced by the variation patterns of the dominant faunistic groups (Gastropoda, Gammaridea, Isopoda and Caridea). Significant positive relationships were found between the biomass of Sargassum and Sargassum+Hypnea with the total density of all faunistic groups (per macroalgae biomass unit). However, the influence of Hypnea epiphytism on the phytal organisms was not evidenced.